2011
DOI: 10.4193/rhino10.261
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal eosinophilia and recurrence of nasal polyps - new classification of chronic rhinosinusitis

Abstract: Background: Eosinophils and nasal polyps are believed to affect the surgical outcome of chronic rhinosinusitis (CRS). CRS is classified based on the presence of nasal polyps in western countries. The majority of patients with CRS with nasal polyps (CRS with NP) are characterized by predominantly eosinophilic inflammation. However, Asian patients with CRS with NP show characteristics indicative of neutrophilic inflammation. Therefore, are eosinophils or nasal polyps more important for the classification of CRS?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(65 citation statements)
references
References 7 publications
0
63
0
2
Order By: Relevance
“…ECRS is characterized by EOS infilitration, which plays a central role in ECRS pathological progress, and it has been indicated that expression of periostin is associated with EOS [ 53 ]. It is not hard to see that eosinophilis can accelerate periostin expression.…”
Section: Periostin In Ecrsmentioning
confidence: 99%
“…ECRS is characterized by EOS infilitration, which plays a central role in ECRS pathological progress, and it has been indicated that expression of periostin is associated with EOS [ 53 ]. It is not hard to see that eosinophilis can accelerate periostin expression.…”
Section: Periostin In Ecrsmentioning
confidence: 99%
“…The literature is rife with different cut-off values to determine mucosal eosinophilia, ranging from >5/hpf to >350/hpf. [7][8][9][10][11][12]18,19 We selected the cut-off value proposed by Kountakis et al, as their immunohistochemical studies for EG2, a marker for activated eosinophils, stained positive in all nasal polyp tissue specimens with more than 5 eosinophils/HPF, while those with 5 eosinophils or less did not stain positive for EG2. 16 Eosinophilic CRSwNP is also associated with decreased likelihood of surgical success and recurrence of disease within 5 years after surgical intervention with a positive predictive value of 87.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the increase of eosinophils in the blood or the presence of eosinophilic infiltrate in tissues is observed in allergic reactions, such as asthma and chronic rhinosinusitis, in helminth infections, and also in some bacterial and fungal infections [179,180]. Immunoregulatory actions for eosinophils, such as lymphocyte recruitment and tissue repair, have also been described [181].…”
Section: Eosinophilsmentioning
confidence: 99%